2021
DOI: 10.3390/su13115813
|View full text |Cite
|
Sign up to set email alerts
|

How Can Rail Use for Leisure and Tourism Be Promoted? Using Leisure and Mobility Orientations to Segment Swiss Railway Customers

Abstract: This study aims to explore how customer segments are characterised by leisure and mobility orientations. By means of a survey, Swiss rail customers’ socioeconomic and trip profiles as well as attitudes towards taking the rail in their leisure time were collected. Respondents were free to take part in the survey by telephone or online, resulting in 1235 full interviews. A principal component analysis followed by segmentation through cluster analysis was conducted to derive their socio-economic and trip profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…For instance, Lam and Hsu (2004) demonstrated that intention to visit Hong Kong was heightened by the positive attitude towards this destination driven by their beliefs that it is a place for shopping, sightseeing and novel experience. Specifically, for studies relating to travel in a liminal space such as luxury cruise and railway tourism, results also exhibit that attitude imposes a positive influence towards behavioural intentions involving readiness to pay a premium price for the experience (Ioana-Daniela et al, 2018) and also increase frequency of patronage (Dang and von Arx, 2021). To the best of our knowledge, there is no known research to examine attitude towards a domestic tourism product such as JHTI 6,5 ATR dining (as opposed to travel destination).…”
Section: Effect Of Motivation On Attitude and Behavioural Intentionmentioning
confidence: 92%
“…For instance, Lam and Hsu (2004) demonstrated that intention to visit Hong Kong was heightened by the positive attitude towards this destination driven by their beliefs that it is a place for shopping, sightseeing and novel experience. Specifically, for studies relating to travel in a liminal space such as luxury cruise and railway tourism, results also exhibit that attitude imposes a positive influence towards behavioural intentions involving readiness to pay a premium price for the experience (Ioana-Daniela et al, 2018) and also increase frequency of patronage (Dang and von Arx, 2021). To the best of our knowledge, there is no known research to examine attitude towards a domestic tourism product such as JHTI 6,5 ATR dining (as opposed to travel destination).…”
Section: Effect Of Motivation On Attitude and Behavioural Intentionmentioning
confidence: 92%
“…As a product, railway tourism should seek to enhance travel experiences, including nostalgia, a sense of history and authenticity. Furthermore, in the experiential travel scene, it is necessary to implement services that can respond to travellers' expectations [16][17][18][19]. These expectations rise when there is an association with the word "luxury" [20,21].…”
Section: Introductionmentioning
confidence: 99%